Distribution of Nature-based Solutions in cities across Europe - Collier, Marcus; Cooper, Clair (My University, 2024)
Nature-based Solutions (NBS) is a conceptual framework that seeks to use properties of nature to co-produce ecosystem services to build climate change resilience and improve quality of life by mitigating the relation- ship between health inequality and socio-economic adversity. This study investigates how the distribution of these forms of urban nature relate to trends in demographic change and social and economic indicators that influence material aspects of quality of life (QoL) in cities. Using macro-scale spatial mapping and descriptive pattern identification, we examine the relationship of distribution trends in the key characteristics of NBS across European cities and social and material factors that influence QoL. Our findings suggest that less than 6% of NBS aim to address poverty or deprivation and fewer than 25% relate to housing or neighbourhood regeneration. We argue inattention to the complex intersectional relationship of socio-economic disparities, historical structural conditions, and the impact of changes to the structural policy on economic convergence across regions leading to the concept being used to address green-growth imperatives in Western Europe rather than mitigate inequalities across eastern and parts of Southern Europe. Failure to address these considerations in the design and deploy- ment of NBS could lead to cities reinforcing or even worsening inequalities within deprived communities, particularly in these areas.
Keywords: Nature-based Solutions; Quality of life; Structural Conditions; Inclusive Society; Smart & Sustainable Planet; CITIES; EUROPE; NATURE-BASED SOLUTIONS; QUALITY OF LIFE; Smart Cities; Structural Conditions